Caribbean Nurse Turnover: A Scoping Review - Rolle-Sands, Shamel; Ingraham, Kenchera (International Journal of Bahamian Studies, 2024)
Nurse turnover in the Caribbean has resulted in continuous shortages and chronic understaffing, jeopardizing the ability of health systems to provide essential services and negatively impacting patient care and outcomes. Despite extensive global research on nurse turnover over the past 40 years, the Caribbean has been largely overlooked by researchers. This study maps and summarizes the existing empirical and grey literature, identifying key themes and knowledge gaps concerning nurse turnover in the Caribbean. We employed Arskey and O’Malley’s methodological approach and collaborated with a health sciences research librarian to develop a search strategy. We searched 12 electronic databases and used Google and Google Scholar to locate relevant literature. Two reviewers independently screened and extracted data, compiling it into qualitative and numerical thematic summaries. The study uncovered a significant scarcity of literature, with only five articles published between 1999 and 2017, mostly quantitative and using cross-sectional methods. Two major themes emerged: mental health challenges and the need for supervisory and organizational support. This review highlights specific predictive factors of turnover intentions among nurses in English-speaking countries of the Caribbean. It also reveals the limited research available on this topic, demonstrating the need to prioritize nursing research on retention and turnover. This study concludes that future researchers should use a multi-disciplinary, geographically wide approach to develop tailored interventions, enhance nurse well-being and promote health system resilience.